Magnetic resonance spectroscopy - Koren, Aleš (Radiology and oncology (Ljubljana), 2002)
Background. Magnetic resonance spectroscopy (MRS) is a comparatively new diagnostic method. Brain tissue is very suitable for MRS analysis. In practice, only a small number of compounds present in the brain may be analysed by MRS. The utility of MRS in neuroradiology and clinical practice isconstantly growing since the investigation is of help in the differential diagnosis of pathological processes as well as in assessing the progress of a disease and evaluating the outcome of treatment. In analysing the data obtained, a number of factors that may influence the objectivity of the resultmust be taken into account. The magnetic resonance scanner located at the Institute of Radiology, University Medical Centre Ljubljana, utilises modern MRS protocols and has proved a valuable tool in the diagnostic evaluation of neurologic diseases. Conclusions. MRS provides spectral analysisof substance in a selected volume of tissue, thereby offering an insight into the metabolic state of the tissue.
Keywords: Adult; Central nervous system diseases; Centralno živčevje, bolezni; Diagnosis; diagnostika; možgani; neurology; Neuroradiography; nevrologija; Nevroradiografija; Nuclear magnetic resonance; nuklearna magnetna rsonanca; Odrasli